BOOK REVIEW: The New Edition of Leland’s Aradia - Magliocco, Sabina (Pomegranate, 1999)
Pazzaglini accurately observes that the Aradia material has very likely been ’de-Christianized’ or ’re-paganised’ because actual Italian folk magical charms all have some Christian content.